Excellent Cyclic and Rate Performances of SiO/C/Graphite Composites as Li-Ion Battery Anode - Hu, Long; Xia, Wenming; Tang, Renheng; Hu, Renzong; Ouyang, Liuzhang; Sun, Tai; Wang, Hui (Frontiers in Chemistry, 2020)
The SiO-based composites containing different carbon structures were prepared from asphalt and graphite by the milling, spray drying, and pyrolysis. In the obtained near-spherical composite particles, the refined amorphous SiO plates, which are coated with an amorphous carbon layer, are aggregated with the binding of graphite sheets. The SiO/C/Graphite composites present a maximum initial charge capacity of 963 mAh g−1 at 100 mA g−1, excellent cyclic stability (~950 mAh g−1 over 100 cycles), and rate capability with the charge capacity of 670 mAh g−1 at 1,000 mA g−1. This significant improvement of electrochemical performances in comparison with pristine SiO or SiO/C composite is attributed to the unique microstructure, in which both the graphite sheets and amorphous carbon coating could enhance the conductivity of SiO and buffer the volume change of SiO. The higher pyrolysis temperature causes the denser spherical microstructure and better cycle life. Our work demonstrates the potential of this SiO/C/Graphite composite for high capacity anode of LIBs.